Individual and person: western and Amerindian concepts about the I - Mariano, Michelle Carlesso [UNESP]; Rodrigues, Alessandro Mariano [UNESP] (Univ Federal Espirito Santo, 2019)
This article will focus on the notion of individual as a Western construction and other ways of conceiving human, especially to what is expressed in Amerindian thought of the Kayapo people. It's from a theoretical synthesis, that matches themes and thinkers of domain of the philosophy with ethnological texts (DUMONT, 1985; MAUSS, 2003; TURNER, 1991,1992). Such analytical project aims to highlight that reductionist conceptions (DESCARTES, 1979; ROUSSEAU, 2000) not enough to explain the multiple complexity to know and to know yourself in the world, which makes it imperative to think of the totality that manifests itself in the lived world while humanity is beyond intradisciplinary domains.
Keywords: Individual; Subjectivity; Decentering; Kayapo